Unorthodox public leadership: the case study of an atypical approach to crisis in Iceland. Issue 1 (8th June 2021) - Gudmundsdottir, Arelia E.; Gudmundsdottir, Svala
Abstract : Purpose: This paper aims to present the case of Jón Gnarr's leadership as he served as a mayor of Reykjavík, the capital of Iceland. The authors' view is that his leadership style illustrates a case study of how a "new" leadership style can emerge in times of crisis. Iceland was significantly affected by the financial crisis in 2008, which led to political and economic crises, which were fuelled by the public's anger and lack of trust. In 2010, Jón Gnarr and his new party, the Best Party, were unexpectedly elected. Before he became known as an unorthodox leader, he worked as a comedian. However, he influenced the discourse in politics in the country and raised trust in the system again while empowering the public managers and simplifying the system while downsizing it. This paper explores and sheds light on the leadership abilities that crises can birth. Design/methodology/approach: This research uses qualitative methods. Seven in-depth interviews were conducted, and the interviewees included Jón Gnarr, three key political leaders who were in office at that time and three executive-level leaders from the city administration. Findings: Evidence suggests that Jón Gnarr and his political party became a part of the political arena due to extreme social and economic factors, which might indicate the factors that can give rise to an unorthodox leader. At the same time, the research portrays the image of a leader that closely matches the theories of authentic leadership, and his leadership style at the time made a lasting impact. When Gnarr stepped into the role of mayor of Reykjavík, he used novel tactics. His political discourse was different; his manner with the public as well as within the system was different. When he became mayor, he demonstrated trust, respect and care as his underlying values. His unorthodox political behaviour appears to have empowered public officials. Thus, gradually, he inspired his followers to change their own communication style. He also addressed traditional political issues such as downsizing, mergers and financial undertakings. Research limitations/implications: Its limitation is that it is difficult to generalize based on one case. Practical implications: The case can shed a light on how unorthodox leadership style can unlock the potential of empowering and trust in a traditional political system. Leaders who dare to be different can raise awareness of those who work within the system as well as the public. Originality/value: This paper contributes to the understanding of authentic and unconventional leadership as an efficient vehicle in unusual circumstances in a public leadership position.